2014
DOI: 10.1128/jvi.00737-14
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus V Protein Interaction with the Antiviral Sensor LGP2 Disrupts MDA5 Signaling Enhancement but Is Not Relevant to LGP2-Mediated RLR Signaling Inhibition

Abstract: The interferon antiviral system is a primary barrier to virus replication triggered upon recognition of nonself RNAs by the cytoplasmic sensors encoded by retinoic acid-inducible gene I (RIG-I), melanoma differentiation-associated gene 5 (MDA5), and laboratory of genetics and physiology gene 2 (LGP2). Paramyxovirus V proteins are interferon antagonists that can selectively interact with MDA5 and LGP2 through contact with a discrete helicase domain region. Interaction with MDA5, an activator of antiviral signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
0
33
0
1
Order By: Relevance
“…The negative regulatory activity of LGP2 is independent of enzymatic activity and remains intact despite mutations that target key helicase domain residues [8, 35, 47, 79]. In contrast, helicase domain mutations disrupt LGP2’s ability to co-activate MDA5 signaling, which requires both ATP hydrolysis and RNA binding [35, 47, 79]. Unlike the RNA-induced activity of other RLRs, LGP2 has a high basal ATP hydrolysis activity that is independent of RNA binding [8, 35].…”
Section: Lgp2mentioning
confidence: 99%
See 1 more Smart Citation
“…The negative regulatory activity of LGP2 is independent of enzymatic activity and remains intact despite mutations that target key helicase domain residues [8, 35, 47, 79]. In contrast, helicase domain mutations disrupt LGP2’s ability to co-activate MDA5 signaling, which requires both ATP hydrolysis and RNA binding [35, 47, 79]. Unlike the RNA-induced activity of other RLRs, LGP2 has a high basal ATP hydrolysis activity that is independent of RNA binding [8, 35].…”
Section: Lgp2mentioning
confidence: 99%
“…For example, we have proposed a working model in which LGP2 switches between MDA5-specific enhancement and a more general RLR negative regulation [47]. Titrating LGP2 expression into MDA5-dependent signaling demonstrates that low levels of LGP2 are synergistic with MDA5 [35, 47, 79, 82], a process that requires LGP2 ATP hydrolysis and RNA binding activities. The MDA5-stimulating activity of LGP2 is revealed in a narrow stoichiometric range, and further titration of LGP2 expression ultimately achieves an inhibitory concentration that disrupts RLR signaling activity [35, 76] [11, 66, 67].…”
Section: Lgp2mentioning
confidence: 99%
“…This model would support the concept that viral evasion mechanisms could evolve to inactivate positive signaling effects of LGP2 in the MDA5 axis, as has been accomplished by paramyxovirus V proteins that antagonize both MDA5 and LGP2. By disrupting LGP2 ATP hydrolysis, V proteins prevent LGP2 RNA recognition, but negative regulatory effects remain intact (77), providing the virus with a double benefit in overcoming host immunity. Although this hypothetical model is currently based on the idea that the concentration of LGP2 determines its differential activity, it is possible and likely that additional research will reveal posttranslational modifications to LGP2 or MDA5 that regulate the switch between positive and negative actions or control more nuanced signaling activities.…”
Section: Lgp2 As a Concentration-dependent Biphasic Switchmentioning
confidence: 99%
“…Viral RNA sequences can change extremely rapidly, and although structural analyses and early functional studies have suggested that RLR-RNA interactions are not strongly affected by sequence variation [52, 84], changes in viral RNA sequences might impact RLR immune signaling under some circumstances [105107]. Many viruses biochemically ‘hide’ their RNAs to avoid host detection [108–110], and viruses are known to antagonize various aspects of the RLR system [111113]. Unfortunately, we know almost nothing about the ecologically important viruses that may have plagued ancient animals, so determining the precise native ligands that may have driven the evolution of RLRs is not possible.…”
Section: Discussionmentioning
confidence: 99%